Development of Canva-Based Interactive Multimedia Using the Addie Model to Enhance Engagement and Critical Thinking Skills in Science Learning - Irma Mulyani; Elly Sukmanasa; Riandi Marisa (Integrated Science Education Journal, 2026)
Purpose of the study: IPAS learning in primary schools still shows low student engagement and weak critical thinking, partly because the media used are not sufficiently interactive. This study develops Canva-based interactive multimedia that is valid, practical, and effective for improving engagement and critical thinking among IV students. Methodology: The research adopts a Research and Development (R&D) approach using the ADDIE model, which consists of five phases: Analysis, Design, Development, Implementation, and Evaluation. Main Findings: The findings indicate that the Canva-based interactive multimedia meets validity criteria and shows good reliability (Cronbach’s Alpha = 0.864), and is categorized as highly practical in the One-to-One Trial (91%), Small Group Trial (94%), and Field Trial (97.5%). Novelty/Originality of this study: The use of the media significantly increased student engagement (emotionally, cognitively, and behaviourally) and improved critical thinking in IPAS learning. Canva-based interactive multimedia is thus effective and appropriate for primary classrooms. Its novelty lies in systematically integrating interactive activities to strengthen engagement and critical thinking, offering a technology-based innovation that supports more active, student-centred learning.